Analytical evaluation of drug package inserts in India - Solanki, Sandip Natwarlal; Chhaiya, Sunita B.; Mehta, Dimple S.; Trivedi, Madhav; Acharya, Tejas; Patel, Dhwani (International Journal of Basic & Clinical Pharmacology, 2017)
Background: A drug package insert or prescribing information is a document provided along with a prescription medication to provide additional information about that drug. Drug package inserts are approved by the administrative licensing authority. A package insert is intended to provide information for the safe and effective use of the respective drug. Product information provided by pharmaceutical companies has been determined to be far from adequate and not conforming with requirement of Indian regulatory. Hence, it was decided to conduct a study to assess the presentation and completeness of clinically important information provided in the currently available package inserts in India. Methods: Package inserts were provided by five pharmacies on request. The package inserts were collected in 10 weeks’ period and then they were analyzed for presentation and completeness of clinical information according to heading mentioned in Section 6.2 and 6.3 of schedule D of Drug and Cosmetic Rule, 1945. If the information was present under relevant heading, it was scored as one. Otherwise as score of zero was assigned. Total score for each heading was calculated by adding the score from the individual package inserts. Results: 70 package inserts were included in the study. None of the reviewed package inserts contained all the sections as required by the Drugs and Cosmetics Act. Total 15 headings were evaluated under both Section 6.2 and 6.3, highest value for the presence of heading were 12 out of 15 heading evaluated. That shows the best value of compliance was 80%. Conclusion: Accurate drug product information is important for the safe and effective use of medicines. Hence, pharmaceutical companies and regulators should ensure that accurate and up to date product information is provided in the package inserts.